The politics of Latin literature : writing, identity, and empire in ancient Rome - Habinek, Thomas N., 1953- (Princeton University Press, 1998)
This is the first book to describe the intimate relationship between Latin literature and the politics of ancient Rome. Until now, most scholars have viewed classical Latin literature as a product of aesthetic concerns. Thomas Habinek shows, however, that literature was also a cultural practice that emerged from and intervened in the political and social struggles at the heart of the Roman world. Habinek considers major works by such authors as Cato, Cicero, Horace, Ovid, and Seneca. He shows that, from its beginnings in the late third century b.c. to its eclipse by Christian literature six hun.